Analysis of Mathematics Learning Difficulties in V Graders of Elementary School of Fraction Material in Terms of Students' Cognitive Level - Putri Puspitasari; Aninditya Sri Nugraheni; Mulyani Mulyani (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2022)
This study aims to analyze the difficulties in learning mathematics in V graders of elementary school in terms of students' cognitive level. This study uses qualitative methods which took class V as subjects based on the classification of high subjects, medium subjects and low subjects. The data taken through learning outcomes, interviews and documentation. The results in this research can be concluded that (1) high subjects (AA) and (NF) do not meet all indicators of difficulty, this is evidenced that high subjects (AA) and (NF) don’t have any difficulty in understanding concepts, principles or formulas and in solving fraction problems. (2) Medium subjects (LU) and (YL) did not meet the two indicators of difficulty. It can be seen they don’t have any difficulty in understanding concepts and applying fractional principles, but they have problems in solving fractional problems in the form of stories. (3) Low subjects (MN) and (BA) fulfill all indicators of difficulty in learning mathematics fraction material by experiencing difficulties in understanding fraction concepts, fraction principles and solving fraction problems. Teachers can implement fun learning if they recognize students' characters and learning styles, use appropriate media or teaching materials, start and end learning with something interesting and fun.